1988
DOI: 10.1161/01.str.19.6.709
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of interobserver variability in a Dutch multicenter study on acute ischemic stroke.

Abstract: Quantitative assessment of patient data is a pertinent part of controlled clinical studies. When several centers are involved, the degree of agreement between different observers becomes important. Therefore, in addition to developing a multicenter study on acute ischemic stroke, we have estimated the interobserver agreement expressed in terms of K statistics. Twelve patients suffering from neurologic deficits due to acute ischemic stroke were examined by four investigators, and the results were assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…9 Our subjects presented with the undifferentiated clinical syndrome of "brain attack," unlike early studies in which stable stroke patients were used and observers were expecting to find neurological symptoms or signs. [3][4][5]7,10 Observers had different levels of experience, which reflects clinical reality (they were not highly trained stroke neurologists, 3,4 nor were the signs demonstrated to the less experienced members of the team by a stroke neurologist 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Our subjects presented with the undifferentiated clinical syndrome of "brain attack," unlike early studies in which stable stroke patients were used and observers were expecting to find neurological symptoms or signs. [3][4][5]7,10 Observers had different levels of experience, which reflects clinical reality (they were not highly trained stroke neurologists, 3,4 nor were the signs demonstrated to the less experienced members of the team by a stroke neurologist 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have measured the inter-rater reliability of elements of the neurological examination, finding it to vary from fair to good. [2][3][4][5][6][7][8][9][10][11] Only 2 studies measured items of the history, and these found surprisingly poor inter-rater reliability. 2,3 No studies have assessed the inter-rater reliability of the clinical diagnosis of stroke (or stroke mimic).…”
mentioning
confidence: 99%
“…31 A study of 344 patients found that low scores predicted early demise but not stroke subtype. 32 Using a slightly modified version of the Mathew scale, considerable interobserver variability was reported in a 12-patient study by Gelmers et al 33 Agreement among investigators ranged from "slight" (K=0.159) for hemianopsia to almost perfect in areas including reflexes and loss of consciousness. The Mathew scale was found to have a low internal consistency (a=0.54) compared with other measures, 31 perhaps suggesting the presence of more than one construct underlying the scale.…”
Section: Physical Deficit Scalesmentioning
confidence: 99%
“…12,19,21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The various items of these scales were submitted to 5 stroke neurologists (A.D.S., J.D.K., R.B., R.-J.V.H., and S.D.R. ), 2 neurolinguistic experts (P.M. and P.P.…”
Section: Scale Developmentmentioning
confidence: 99%